복숭아 품종과 부위별 비타민 C, 안토시아닌 및 카로티노이드 함량 분석 - 김지영(Ji Yeong Kim); 권수현(Su Hyun Kwon); 장미(Mi Jang); 이지윤(Ji Yun Lee); 김기창(Gi Chang Kim); 강해주(Hae Ju Kang); 황인국(In Guk Hwang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2021)
본 연구에서는 백도 계통(8종)과 황도 계통(8종) 복숭아의 과육 및 껍질 부위에 함유된 ascorbic acid, anthocyanin, carotenoid 함량을 비교･분석하였다. Ascorbic acid 분석 결과 백도 껍질 부위는 과육 부위보다 약 2배 높은 6.70 mg/100 g FW의 ascorbic acid 함량을 나타냈고, 황도의 경우 과육과 껍질 간의 유의미한 함량 차이는 없었다. 또한 황도와 백도를 비교하였을 때 백도 껍질이 황도 껍질보다 유의적으로(P<0.01) 높은 함량을 보였으며 과육 간의 유의미한 차이는 없었다. Anthocyanin 성분 중 cyanidin-3- glucoside(C3G)와 cyanidin-3-rutinoside(C3R) 분석 결과, C3G가 복숭아에 함유된 주요 anthocyanin임을 확인하였으며 백도 껍질 부위가 과육 부위보다 유의적으로(P<0.01) 높은 함량을 보였고 황도 또한 껍질 부위가 과육 부위보다 높은 C3G 함량을 나타냈다. 황도와 백도를 비교하였을 때 백도 과육이 황도 과육보다 유의적으로(P<0.05) 높은 C3G 함량을 보였으며 백도 껍질과 황도 껍질 간의 유의미한 차이는 나타나지 않았다. Carotenoid 성분 중 lutein, zeaxanthin, β-cryptoxanthin, α-carotene, β-carotene 분석을 실시하였으며, 이 중 β-carotene의 함량이 주요 carotenoid 성분으로 확인되었다. 백도 껍질의 평균 β-carotene 함량은 과육 평균 함량보다 약 13배 높은 함량을 보였고 황도 껍질의 평균 β-carotene 함량 또한 과육 평균 함량보다 약 4배 높은 함량을 보였으며, 황도와 백도를 부위 별로 비교하였을 때 황도의 껍질 및 과육 부위가 백도의 껍질 및 과육 부위보다 높은 경향을 보였다. 현재 국내 복숭아 품종의 기능성분에 대한 연구 진행이 미흡하기 때문에 본 연구 결과가 향후 복숭아 식품 연구와 신품종 개발에 있어 필요한 기초자료로 활용될 수 있을 것이다. Peaches (Prunus persica L. Batsch) are one of the commonly consumed fruits. Depending on the color of the flesh, peaches are typically classified into white and yellow varieties. To identify the differences in the content of the functional components according to the cultivar and its parts, the ascorbic acid, anthocyanin and carotenoid content were analyzed. The results showed that the content of ascorbic acid was higher in the peel than the flesh of the white peaches and there was no significant difference between the flesh and peel of yellow peaches (P>0.05). Anthocyanin analysis showed that cyanidin-3-glucoside was higher in the peel than the flesh in both yellow and white peaches. Cyanidin-3-rutinoside was detected only in the peel of yellow and white peaches. In the case of carotenoids, lutein, zeaxanthin, β-cryptoxanthin, α-carotene, and β-carotene were analyzed. All the carotenoid components showed a higher content in yellow peaches than white peaches. In particular, the content of β-carotene was the highest. The content of β-carotene was higher in the peel than the flesh in both yellow and white peaches, and a higher content was detected in the yellow peaches compared to the white peaches. The differences in content were found to be significant according to the cultivars as well as the farms and regions (P<0.05). Through this study, the content of functional components according to the cultivar and its parts was confirmed, and it is expected that this data will be widely used in the development of functional health foods through additional research. KCI Citation Count: 3